Connectivity among leatherback turtle populations in the Indian Ocean and West Pacific: a new management unit proposed in Sumatra, Indonesia - As-singkily, Maslim; Dutton, Peter H.; van Hoof, Venus; Zai, Meriussoni; Murniadi,; Nijland, Reindert; Becking, Leontine E. (Frontiers in Marine Science, 2025)
Leatherback turtles (Dermochelys coriacea) are highly migratory and globally distributed, yet exhibit low overall genetic diversity. Currently, the species is divided into seven Regional Management Units (RMUs), and significant gaps remain in understanding genetic connectivity within the Indo-Pacific, particularly the Northeast Indian Ocean. Here, we investigate the genetic diversity and population structure of leatherback turtles sampled from five nesting sites in Sumatra, Indonesia. Using mitochondrial DNA (mtDNA) control region sequences from 57 individuals, we identified eight haplotypes, including one novel variant, with Sumatra exhibiting the highest haplotype (h = 0.786) and nucleotide diversity (π = 0.0040) among regional rookeries. There was a lack of significant stock structure based on our haplotype frequency data among rookeries in Sumatra (p>0.05). Phylogenetic and haplotype network analyses revealed that Sumatra contains lineages from both Indian and West Pacific Ocean clades, suggesting its role as a genetic bridge between these populations. Our results on population genetic structure support the recognition of Sumatra as a distinct Management Unit (MU), separate from other Northeast Indian Ocean populations. Our findings highlight the need to refine existing RMU boundaries and prioritize conservation actions in Sumatra to preserve its unique genetic composition and enhance connectivity across the Indo-Pacific.